2007
DOI: 10.1111/j.1601-0825.2006.01344.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia and interleukin‐1β on expression of tenascin‐C in temporomandibular joint

Abstract: These results indicate that hypoxic conditions with inflammation modulate the tenascin-C expression in synovial fibroblasts, but not in disk cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
(33 reference statements)
1
17
0
2
Order By: Relevance
“…A disrupted nutrient supply has long been implicated in the development of IVD disc degeneration, including cartilage end-plate calcification and a further decrease in oxygen and glucose levels. In TMJ disc cells, recent studies have shown that hypoxia with inflammation modulates the gene expression of tenascin-C and matrix metalloproteinases 17, 18 . However, unlike the chondrocytes and IVD cells, the effect of essential nutrients (e.g., oxygen and glucose) on the energy metabolism and matrix synthesis of TMJ disc cells is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A disrupted nutrient supply has long been implicated in the development of IVD disc degeneration, including cartilage end-plate calcification and a further decrease in oxygen and glucose levels. In TMJ disc cells, recent studies have shown that hypoxia with inflammation modulates the gene expression of tenascin-C and matrix metalloproteinases 17, 18 . However, unlike the chondrocytes and IVD cells, the effect of essential nutrients (e.g., oxygen and glucose) on the energy metabolism and matrix synthesis of TMJ disc cells is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The balance between the rate of nutrient transport through the matrix and the rate of consumption by disc cells establishes a concentration gradient across the disc. The concentration levels of essential nutrients, such as oxygen and glucose, can profoundly affect disc cell viability, matrix synthesis, and response to inflammatory factors (Yamaguchi et al, 2005;Tojyo et al, 2008). This suggests that deviation from physiological nutrient levels in the TMJ disc due to the lack of nutrient supply may initiate tissue remodeling and matrix degradation.…”
Section: Introduction Tmentioning
confidence: 99%
“…After 3, 5 and 9 days in culture, fibronectin, collagens I and IV, Lysyl Oxidase ( LOX ), Lysyl Oxidase Like-2 ( LOXL2 ) and VEGFA mRNA expression were quantified in hypoxia and atmospheric-exposed co-cultures. These genes were chosen as they have been shown to be regulated by hypoxia and play an important role in ECM organization and stability and angiogenesis [6, 7, 15-24]. We found that collagen 1αI and LOX mRNA were upregulated in response to hypoxic as compared to atmospheric conditions, while collagen IV, fibronectin, VEGFA, and LOXL2 mRNA were largely downregulated in response to hypoxic as compared to atmospheric conditions (Figure 2).…”
Section: Resultsmentioning
confidence: 94%
“…For instance, we have recently shown that hypoxia increases the expression of collagens I and IV, laminin and fibronectin deposition from ECs [15]. Similarly, others have shown using fibroblasts and animal models that hypoxia increases collagen I mRNA expression, synthesis and deposition [16-20], fibronectin protein expression [21,22], collagen IV mRNA expression and secretion [21,23], and tenascin-C mRNA and protein expression [24]. In addition to these, hypoxia has also been reported to influence the expression of prolyl hydroxylases and lysyl oxidases (LOX), enzymes which stabilize and promote crosslinking of collagens and elastins in the ECM [25].…”
Section: Introductionmentioning
confidence: 97%